Programmable Minecraft: a tool to learn programming in high school - Zabala, Gonzalo; Pérez Cerrato, Laura; Blanco, Sebastián; Morán, Ricardo; Teragni, Matías (Universidad Nacional de Córdoba, Faculdad de Ciencias Sociales, Centro de Estudios Avanzados. Maestría en Procesos Educativos Mediados por Tecnología, 2016)
The rise of smart devices which in one way or another have an internal software development (mobile phones, home appliances, cars, among others), has increased the need for programmers. Since formal education has not been successful in meeting this need, several projects with tools that enable to learn programming in a simple and entertaining way have arisen, such as The Hour of Code (http://code.org), which bases its tutorials in different games. Following this trend, a variant of Minecraft, which allows creating and modifying the behavior of its objects in real-time using Smalltalk as a language, was created.